Introduction to a Wales project for evaluating residential retrofit measures and impacts on energy performance, occupant fuel poverty, health and thermal comfort. (October 2017) - Littlewood, J.R.; Karani, G.; Atkinson, J.; Bolton, D.; Geens, A.J.; Jahic, D.
Abstract: This paper discusses a Knowledge Economy Skills Scholarship two (KESS2) under the Low Carbon, which crosses the Energy and Environment and also the Lifesciences and health economic priority areas of the Welsh Government and is to be undertaken by the final author under the guidance of the other authors. The KESS2 project will evaluate retrofit measures on upgrades to dwelling from the Arbed 1, 2 and 3 programmes in Wales, and also assess impacts upon energy performance, and occupant fuel poverty, health and wellbeing and thermal comfort. The significance of the research is that there are no other studies that address all these parameters; indeed, much of the work to date in the UK is focused upon investigating impacts upon the dwellings. The KESS2 project led by Cardiff Metropolitan University is undertaken and co-funded in collaboration with Being Greener at Melin Homes and builds upon a successful KESS1 project that evaluated the construction quality of retrofitted exterior wall insulation (EWI) on dwellings where the occupants were in fuel poverty between 2010 and 2014. Context to the academic, scientific and industrial challenges are discussed, as is the programme of work and the expected outcomes. This paper will be useful for academics, landlords of housing stock undergoing retrofit measures and government agencies funding retrofit upgrades to dwellings.